Characterization assessment on nanofiltration membrane using steric-hindrance pore (SHP) and teorell-meyer-sievers (TMS) models - Mazrul Nizam Abu Seman,; Nora’aini Ali,; Nurul Ain Jalanni,; Che Ku Muhammad Faizal Che Ku Yahya,; Norhafiza Ilyana Yatim, (Universiti Kebangsaan Malaysia, 2023)
Interfacial polymerization (IP) is a simple process for modifying thin-film composite (TFC) polymers that can be used as separation membranes in water treatment. This work describes the IP process for the preparation of polyester TFC membranes using organic monomers, in particular triethanolamine (TEOA) and trimesoyl chloride (TMC). This work includes an evaluation of monomer concentration and polymerization reaction time as variables to determine the membrane properties and its performance as acid humic removal. The characterization of TFC membranes was investigated using field emission scanning electron microscopy (FESEM), steric hindrance pore (SHP) and Teorell-Meyer-Sievers model (TMS). This IP technique resulted in the membrane (NF-PES8-35) having the lowest contact angle (θ=34.0±0.35) and lower hydrophobicity (θ=62.6 ± 0.33) compared to the unmodified membrane. The rejection of NaCl by NF-PES8-35 membrane showed the highest 0.001 M NaCl (62.42%), while NF-PES4-15 membrane showed the lowest (2.4%). The highest removal of humic acid (97.8%) was achieved when separation was performed with the NF-PES6-35 membrane and the high performance polyester TFC membranes were exhibited in the water purification filtration system.